Unique electronic and structural properties of 1,4-Benzoquinones : crystallochemistry of alkali chloranilate hydrates - Molčanov, Krešimir (Array, 2009)
Summary: The unique electronic and structural characteristics of 1,4-benzoquinones with possibilities for numerous interactions such as coordination, hydrogen bonding accompanied by proton and/or electron transfer, teta-interactions, and redox activity, are used by nature to perform important biological reactions. In spite of their wide use in supramolecular chemistry for construction of functional materials, the intercor-relation of their versatile interactions has not been completely evaluated. The impacts of hydrogen bonding and cations on interactions of quinoid skeleton are studied on the prepared series of alkali (Li+, Na+, K+, NH4+ and Rb+ chloranilate hydrates, and anhydrous caesium homologue. The π---π stacking interactions of chloranilate dianions observed in the structures of sodium chloranilate dihydrate and caesium sodium chloranilate monohydrate [with centroid separation distances of 3.662(1) and 3.740(2) A and shifts of 1.698 and 1.358 A, respectively] are tuned by hydrogen bonding involving water molecules. The crystal structures of potassium and rubidium chloranilate monohydrates are isostructural whereas their ammonium homologue, due to the presence of cation with pronounced proton-donor activity, exhibits completely different hydrogen bonding network. In the six of seven structures studied chloranilate dianion reveals the crystallographic symmetry Ci